Review of lab diagnosis in modern era, current instruments used for diagnosis of hepatitis - Mahrukh; Shabia Anjum; Safa; Sana Maryum (AMMANIF, 2021)
Viral hepatitis is a global public health problem, particularly in developing countries due to its persistent circulation in the environment. The improved sanitary condition, increase in awareness of personal hygiene and other precautionary measures have led to the marked reduction in transmission of hepatitis. There are various causes for different types of hepatitis. Hepatitis B and hepatitis C are more prevailing types of hepatitis. Various types of diagnostic tests are being performed including serologic tests (to detect antibody in serum) and molecular tests (to analyze biological markers in the genome and proteome), which vary with the type of hepatitis. The development of detection techniques possessing the requisite sensitivity and specificity for the practical routine monitoring purposes is of great importance necessary for the protection of public. Mostly PCR and ELISA are used for performing diagnostic tests. PCR are very expensive techniques and used by higher labs and hospitals.